Multimedia as a Learning Tool in Training Reading Skills of Elementary Schools Students - Siregar, Epi Supriyani; Kurniati, Rizki; Rahayu, Sri (Journal of Education Technology, 2022)
Reading comprehension is a dual activity that requires various cognitive and linguistic processes to complete. This is the result of two skill sets namely: decoding and linguistic comprehension. It covers the differences in reading comprehension and provides a useful basis for classifying reading difficulties. This study aims to develop multimedia as a learning tool in training the reading skills of elementary school students. The subjects of this study involved 30 grade 5 students at the elementary school level. This research uses a research and development (R&D) approach, through a Gall & Borg development study. Data collection techniques were carried out through interviews and observations for non-test databases and formative and summative evaluations for testing the effectiveness of the developed media which were included in the test category. The data analysis technique used in this study uses several stages which include; transcription, verification, and coding data from all test and non-test data that have been collected. The learning model is integrated with various learning tools (multimedia) including student and teacher books, as well as lesson plans (RPP). Based on the data obtained, it is known that multimedia integrated with the inquiry learning model is effective in improving student learning outcomes than without using multimedia. The findings of this study provide a fundamental reference for thinking about reading comprehension and its growth by emphasizing the importance of decoding in reading.